'Attending IFLA was Amazing': Benefits of Conference Attendance as Reported by Delegates*. Issue 1 (2nd January 2017) - Dumbell, Petra
Abstract: A large amount of time and resources is spent every year in the library and information science (LIS) sector in Australia to organise, fund and attend conferences. However, the possible benefits of conference attendance for librarians have not been a focus of research in the field. This article, reporting on the findings of a pilot study conducted in the context of a PhD research project, addresses this gap and analyses conference attendance benefits as reported by librarians who attended a specific international conference. The findings of this study link directly to issues and themes that are relevant to all library sectors in Australia.